2023
DOI: 10.15403/jgld-4634
|View full text |Cite
|
Sign up to set email alerts
|

Bile Composition - which Components Can Have Clinical Significance? A Review of the Literature

Abstract: Over the years, scientific research concerning the qualitative analysis of bile and its use in diagnostics and treatment, have been very limited. Due to unsatisfactory results of detection, inter alia, cholangiocarcinoma or gallbladder carcinoma, and the necessity to discover more efficient techniques of diagnostics, bile has become an interesting direction to study. Nowadays, thanks to the latest research, analysis of concentration i.e. specific bile salts, proteins, nucleic or fatty acids in bile or imbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Traditional culture techniques suggested that the biliary tract was sterile, but metagenomic analysis using pyrosequencing of bacterial 16S rRNA genes revealed a diverse bacterial population in the biliary system [ 20 , 32 , 33 ]. This microbial population seems to originate from the gut, and its imbalance or dysbiosis has been associated with inflammatory and malignant biliary diseases [ 11 , 20 , 34 , 35 ]. Some evidence for this link is the presence of bacteria (e.g., Helicobacter bilis ) in gallstones, the production of autoantibodies against biliary epithelial cell proteins that have molecular mimicry with bacterial proteins in primary biliary cirrhosis or primary sclerosing cholangitis, and the overgrowth of specific enteric bacteria in cholangiocarcinoma [ 16 , 36 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional culture techniques suggested that the biliary tract was sterile, but metagenomic analysis using pyrosequencing of bacterial 16S rRNA genes revealed a diverse bacterial population in the biliary system [ 20 , 32 , 33 ]. This microbial population seems to originate from the gut, and its imbalance or dysbiosis has been associated with inflammatory and malignant biliary diseases [ 11 , 20 , 34 , 35 ]. Some evidence for this link is the presence of bacteria (e.g., Helicobacter bilis ) in gallstones, the production of autoantibodies against biliary epithelial cell proteins that have molecular mimicry with bacterial proteins in primary biliary cirrhosis or primary sclerosing cholangitis, and the overgrowth of specific enteric bacteria in cholangiocarcinoma [ 16 , 36 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to plasma biomarkers, bile components may provide useful information for diagnosing biliary tract diseases. Recent investigations have explored the possibility of using specific bile salts, proteins, nucleic acids, fatty acids, or microbiome-derived products as biomarkers [ 34 ]. In this context, we found that the bile level of corisin was significantly elevated in AC patients with severe disease compared to non-severe AC patients.…”
Section: Discussionmentioning
confidence: 99%